A casa del sarto. Appunti di lettura dai Promessi sposi (ACME, 2021)
The character of Manzoni’s tailor has collected by literary critics too many diminishing interpretations: the perspective we have assumed aims instead at a reconsideration, within a global reading of Promessi sposi, of the specifically literary meaning that the character would claim for himself. The hypothesis is to grasp, inside the middleclass house, a thin but tenacious thread, hidden but intentional, able to tie the analyzed episode to the actual conclusion of the novel. It’s almost as the narrator, at such a height of heroic effort, had already imagined a good woman cooking the sugo of the whole story in advance, the capon broth for the feast day. As a confirm of the intuition, multiple signals of light appeared - metanarrative light - or clear invitations to recognize, in the former Tommaso Dalceppo, no less than one of Manzoni’s possible textual stuntmen.